Good Morning Vietnam - Harkison, Tracy; Goh, Sandra (The School of Hospitality & Tourism, Auckland University of Technology, 2020)
The following is a reflection from two Auckland University of Technology (AUT) academics seconded as visiting professors to teach events and human resource management at a Vietnamese university. As this may be an ongoing project for AUT, they have provided these insights to guide other academics venturing to teach in Vietnam.
It was a humbling experience and we recommend all academics make teaching overseas and entering into global classrooms part of their journey. Although others with experience of overseas teaching have recommended co-teaching with a translator/interpreter [1], interpreters are not always available when required. And when surprised by their absence, what do you do? Ten lessons were drawn from our experiences for you to include in your overseas teaching survival kit:
Lesson #1. Expect the unexpected.
Lesson #2. Brace yourself for culture shock – the first day you will feel like a fish out of water, which really makes you reset yourself to becoming a better teacher. Imagine you are without an interpreter and the students can only understand half of your slides.
Lesson #3. Adapt your materials and revise your notes to include local examples. This will involve thinking on your feet; your assessment format may undergo many changes. Try to blend in your students’ local and pop-cultural interests.
Lesson #4. Find your allies; the class monitor and the interpreter rule! Identify the ‘leaders of the pack’ – those who can help lead and manage the class.
Lesson #5. Use language carefully. Remember that English words can have more than one meaning and that you will spend most of your time rephrasing sentences.
Lesson #6. Co-teaching with an interpreter means half the time is spent translating your lessons. Be realistic about your learning outcomes.
Lesson #7. There are no international standards in Vietnam, only regional standards. For example, the international hotel accreditation is not the same as Vietnam’s hotel quality standards.
Lesson #8. Be prepared with multiple, fun teaching tools to engage your students in group activities. Team building is always welcome.
Lesson #9. Bring small souvenirs from New Zealand as little treats and rewards to encourage participation from students.
Lesson #10. Always travel in pairs and be prepared to ‘rough it’.
Vietnam has transformed us into instructors with a global perspective. We went to impart knowledge, but we have had returned to us many times what we gave. We stepped outside of our comfort zones and this has certainly stretched our personal and professional limits in ways conventional teaching could never achieve. Like Stachowski and Sparks [2], we now know what it is to be cultural outsiders looking in, and how to find ways to gain acceptance as ‘foreign teachers’. Now that we are back on campus comfortably teaching in English, we should still consider the students we have in our classrooms. In a university that promotes the presence of a global community, we need to be mindful that some international students in our classrooms may need help to orientate them to what, for them, is an alien learning and teaching platform in a foreign language.
This teaching reflection was supposed to be written upon our return from Vietnam in November 2019. However, at the time of writing, COVID-19 has brought about unprecedented changes that are transforming the way universities are teaching – bringing their lessons online to students from all over the world. Although this article is not focused on COVID-19, the unusual times have triggered questions for academics and industry trainers planning on teaching overseas in the future, to consider beyond the above lessons, particularly about the accessibility of technology. Considerations include the availability of hardware and software to students in other countries. We did not have access to WIFI in the classrooms in Vietnam; students were dependent on their phones for the additional information they needed for our group activities.